CMOS front ends for millimeter wave wireless communication systems - Deferm, Noël; Reynaert, Patrick (Analog Circuits and Signal Processing,, 2015)
This book focuses on the development of circuit and system design techniques for millimeter wave wireless communication systems above 90GHz and fabricated in nanometer scale CMOS technologies. The authors demonstrate a hands-on methodology that was applied to design six different chips, in order to overcome a variety of design challenges. Behavior of both actives and passives, and how to design them to achieve high performance is discussed in detail. This book serves as a valuable reference for millimeter wave designers, working at both the transistor level and system level.   Discusses advantages and disadvantages of designing wireless mm-wave communication circuits and systems in CMOS; Analyzes the limitations and pitfalls of building mm-wave circuits in CMOS; Includes mm-wave building block and system design techniques and applies these to 6 different CMOS chips; Provides guidelines for building measurement setups to evaluate high-frequency chips.  .